Icelandic salted cod in Madrid : brand audit - Kristinn Björnsson 1982- (2015)
The subject of this research is the brand equity of Icelandic bacalao (salted cod) in Madrid. Bacalao is an immense part of Spanish culinary tradition. Spain has for a long time been one of the most important markets for exported Icelandic bacalao. Although there has been a gradual decline in consumption of traditional bacalao in Spain, substitute products such as light-salted cod have been expanding the market. Madrid represents one of the most important bacalao markets in Spain, but Icelandic bacalao has always held a relatively weak market position there, compared to some of its competitors. Conjoint marketing efforts, aimed at fortifying the brand of Icelandic bacalao as a whole are led by Íslandsstofa (Promote Iceland). It is of considerable value to the Icelandic economy to maintain and strengthen its status as the market leader. Still, little research has been conducted to provide insights that can optimize the brand management of Icelandic bacalao for the Spanish consumer. In 2013, a brand audit for Icelandic bacalao was conducted by Kristinn Arnarson. It measured brand awareness and brand image of Icelandic bacalao in Barcelona, Spain. This study utilizes a consumer survey and in-depth interviews with chefs in Madrid to provide comparative results, but for the Madrid area. Further, its aim is to bridge a gap in knowledge in whether or not consumers clearly distinguish between traditional and light-salted bacalao and how they perceive these products. Lastly, the study provides understanding of which value propositions should be emphasized in marketing communication in Spain. The main conclusions are that in comparison with Barcelona, Icelandic bacalao holds a relatively weak brand awareness and brand image within the Madrid market. Professionals know the Icelandic bacalao and rate it highly, but not higher than its Norwegian and Faroese counterpart. Consumers claim to know the difference between traditional and light-salted bacalao, but this terminology is very unclear to them. Iceland should emphasize ...